Rehabilitation after new coronavirus infection (COVID-19): principles and approaches - Marina G. Bubnova (Concilium Medicum, 2021)
The novel coronavirus infection (COVID-19), which quickly became a pandemic in 2020, has presented new challenges for healthcare system. COVID-19, being a contagious infectious disease predominantly affects respiratory system, causes cardiovascular, neurocognitive, renal, gastrointestinal, hepatic, metabolic and mental damages, which is in fact a multisystem disease. Patients with COVID-19, primarily with moderate and severe forms, need appropriate rehabilitation. This article establishes need of development of rehabilitation programs for COVID-19 patients, identifies their problems that leads to restrictions on everyday life, self-service, mobility, communication, interpersonal relationships, and professional activities. Goals and general principles of medical rehabilitation in context of a pandemic at all three stages are presented. Features of rehabilitation approaches are highlighted and important components of individual rehabilitation program for COVID-19 patients are highlighted.